RAHASIA SUKSES PENDIDIKAN KELUARGA ISLAMI: MENANAMKAN NILAI-NILAI QURANI DAN HADITS PADA ANAK - Firmansyah, Didi; Fitriani Fauziah; Murzal (Indonesian Society and Religion Research, 2025)
Abstract: : Child education is the main foundation in shaping a generation of noble character. The family, as the smallest unit in society, plays a crucial role in this educational process. The Qur'an and Hadith, as the primary sources of Islamic teachings, provide comprehensive guidance on the principles of child education. This research aims to examine effective strategies in instilling Quranic and Hadith values in children within the context of Muslim families. Through a qualitative approach with literature study, this research analyzes relevant verses of the Qur'an and Hadith regarding child education, as well as explores best practices in their implementation. The research results show that the internalization of Quranic and Hadith values can be achieved through parental role modeling, positive behavior habituation, and creating an Islamic family environment. This research contributes to the development of a holistic and sustainable model of Islamic family education.